Auxin analysis using laser microdissected plant tissues sections - Luz G. Muñoz-Sanhueza; YeonKyeong Lee; Molly Tillmann; Jerry D. Cohen; Anne Kathrine Hvoslef-Eide (BMC Plant Biology, 2018)
Abstract Background Quantitative measurement of actual auxin levels in plant tissue is complimentary to molecular methods measuring the expression of auxin related genes. Current analytical methods to quantify auxin have pushed the limit of detection to where auxin can be routinely quantified at the pictogram (pg) level, reducing the amount of tissue needed to perform these kinds of studies to amounts never imagined a few years ago. In parallel, the development of technologies like laser microdissection microscopy (LMD) has allowed specific cells to be harvested from discrete tissues without including adjacent cells. This method has gained popularity in recent years, especially for enabling a higher degree of spatial resolution in transcriptome profiling. As with other quantitative measurements, including hormone quantifications, sampling using traditional LMD is still challenging because sample preparation clearly compromises the preservation of analytes. Thus, we have developed and validated a sample preparation protocol combining cryosectioning, freeze-drying, and capturing with a laser microdissection microscope to provide high-quality and well-preserved plant materials suitable for ultrasensitive, spatially-resolved auxin quantification. Results We developed a new method to provide discrete plant tissues for indole-3-acetic acid (IAA) quantification while preserving the plant tissue in the best possible condition to prevent auxin degradation. The method combines the use of cryosectioning, freeze-drying and LMD. The protocol may also be used for other applications that require small molecule analysis with high tissue-specificity where degradation of biological compounds may be an issue. It was possible to collect the equivalent to 15 mg of very specific tissue in approximately 4 h using LMD. Conclusions We have shown, by proof of concept, that freeze dried cryosections of plant tissue were suitable for LMD harvest and quantification of the phytohormone auxin using GC-MS/MS. We expect that the ability to resolve auxin levels with both spatial- and temporal resolution with high accuracy will enable experiments on complex processes, which will increase our knowledge of the many roles of auxins (and, in time, other phytohormones) in plant development.